Induction of labour after 37 weeks of pregnancy using foley’s catheter: traction versus non-traction method - Bhatu, Jaydeep J.; Patel, Disha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Cervical Foley’s catheter used now a days for induction of labour alone as well as a combined with cerviprim gel. The objective of the study was to assess the effectiveness of 750 cc traction on Foley catheter with no traction for labour induction in >37 weeks pregnancy. Methods: A randomized controlled trial performed on pregnant women at >37 weeks who were admitted for induction of labour with unfavourable cervix. They were randomly assigned into two groups, Foley’s with 750 cc traction and without traction. The primary outcomes were improvement in Bishop Score, number of favourable cervix following induction and the mode of delivery. The secondary outcomes were neonatal outcome, and maternal infection. Results: A total of 80 pregnant women were randomized into traction group (n=46) and non-traction group (n=34). Traction group had significantly (p=0.0462) higher number of vaginal delivery compared to non-traction group. Participants were comfortable using both methods. There was no difference in neonatal outcomes and risk of maternal infections in both groups. Conclusions: Application of traction did result in more vaginal delivery.